Adverse maternofoetal outcomes associated with ionised calcaemia, total calcaemia, albuminaemia, and calcium supplementation in pregnancy: Analysis from a resource-limited setting. - Atem Bethel Ajong; Bruno Kenfack; Innocent Mbulli Ali; Martin Ndinakie Yakum; Prince Onydinma Ukaogo; Fulbert Nkwele Mangala; Loai Aljerf; Phelix Bruno Telefo (PLoS ONE, 2022)
Introduction Disorders of total calcium (tCa) in pregnancy have been associated with adverse maternofoetal outcomes. However, studies evaluating this from the viewpoint of ionised calcaemia are practically inexistent. This study estimates the prevalence of some adverse maternal and foetal outcomes and the potential effect of ionised calcium (iCa), tCa, albumin and calcium supplementation on some maternofoetal outcomes. Methods A cross-sectional study was conducted among 1074 pregnant women in late pregnancy from four health facilities in the Nkongsamba Health District. Data were collected by interview, analysis of maternal blood samples and measurement of maternal and foetal parameters. Total calcaemia and albuminaemia were measured by atomic absorption spectrophotometry, while iCa and pH were measured using ion-selective potentiometry. Associations were measured using the odds ratio in simple and multiple logistic regression. Results The prevalence of low birth weight, macrosomia, and hypertension in pregnancy was 6.27 [4.97-7.89]%, 4.78 [3.65-7.89]%, 10.24 [8.57-12.20]%, respectively. Following multiple logistic regression, women with iCa levels ≤ 1.31mmol/L had significantly increased odds of hypertension in pregnancy (AOR = 2.47 [1.63-3.74], p-value = 0.000), having babies with low birth weight (AOR = 2.02[1.33-3.61], p-value = 0.002), low birth length (AOR = 2.00 [1.34-2.99], p-value = 0.001), low brachial circumference (AOR = 1.41[1.10-1.81], p-value = 0.007), first minute Apgar score < 7 (AOR = 3.08[1.70-5.59], p-value = 0.000) and fifth minute Apgar score < 7 (AOR = 2.86[1.32-6.16], p-value = 0.007). Ionised calcaemia had no significant association with maternal body mass index immediately after birth and the head circumference of the baby. Total calcaemia was found to have no significant association with any of the selected outcomes, while women with total albuminaemia ≤ 30mg/L had significantly higher odds of having babies with low birth weight (AOR = 3.40[1.96-5.91], p-value = 0.000), and Apgar scores < 7 at the first (AOR = 2.07[1.16-3.70], p-value = 0.013). Calcium supplementation showed no significant association with any of the selected outcomes except for the first (OR = 0.42[0.24-0.72], p-value = 0.002) and fifth minute Apgar score (OR = 0.25[0.12-0.50], p-value = 0.000). Conclusion The prevalence of low birth weight, macrosomia, and hypertension in pregnancy was 6.27 [4.97-7.89]%, 4.78 [3.65-7.89]%, 10.24 [8.57-12.20]%, respectively. Maternal iCa levels ≤ 1.31mmol/L significantly increase the odds of having babies with low birth weight, low birth length, low brachial circumference at birth, low Apgar scores at the first and fifth minutes and maternal hypertension in pregnancy. Low maternal albuminaemia is significantly associated with low birth weight, and Apgar score < 7 at the first minute. None f the selected maternofoetal outcomes directly depend on total calcaemia, given that none of the associations was statistically significant. Even though iCa levels remain relatively normal in normal pregnancies, it remains the strongest predictor of foetal outcomes. Calcium supplementation significantly improves the Apgar scores at the first and fifth minute. Routine pregnancy follow-up should include evaluating maternal calcaemic states, particularly the ionised fraction, to detect the low-normal concentrations likely to impact maternal and foetal outcomes. Normal iCa levels for pregnant women need revisiting.